Fuzzy Adaptive Nonsingular Fixed-Time Attitude Tracking Control of Quadrotor UAVs - Chen, Qiang; Tao, Meiling; He, Xiongxiong; Tao, Liang (IEEE transactions on aerospace and electronic systems, 2021)
In this article, a fuzzy adaptive nonsingular fixed-time attitude tracking control scheme is proposed for the quadrotor unmanned aerial vehicles (UAVs) subject to inertia uncertainties, actuator saturation, and faults. A new nonsingular fixed-time sliding mode surface and an auxiliary function are constructed, such that the singularity problem can be avoided in the controller design without using any piecewise continuous functions. Then, a novel arccot function-based double power reaching law is developed to adjust the control gain and enhance the transient tracking performance. The fixed-time convergence of sliding variables and tracking errors are analyzed by rigorous theoretical proofs, and comparative experiments on a three-degree-of-freedom quadrotor platform are performed to illustrate the effectiveness of the presented scheme.